Long‐term antagonistic effect of increased precipitation and nitrogen addition on soil respiration in a semiarid steppe. Issue 24 (9th November 2017) - Han, Hongyan; Du, Yue; Hui, Dafeng; Jiang, Lin; Zhong, Mingxing; Wan, Shiqiang
Abstract: Changes in water and nitrogen (N) availability due to climate change and atmospheric N deposition could have significant effects on soil respiration, a major pathway of carbon (C) loss from terrestrial ecosystems. A manipulative experiment simulating increased precipitation and atmospheric N deposition has been conducted for 9 years (2005–2013) in a semiarid grassland in Mongolian Plateau, China. Increased precipitation and N addition interactively affect soil respiration through the 9 years. The interactions demonstrated that N addition weakened the precipitation‐induced stimulation of soil respiration, whereas increased precipitation exacerbated the negative impacts of N addition. The main effects of increased precipitation and N addition treatment on soil respiration were 15.8% stimulated and 14.2% suppressed, respectively. Moreover, a declining pattern and 2‐year oscillation were observed for soil respiration response to N addition under increased precipitation. The dependence of soil respiration upon gross primary productivity and soil moisture, but not soil temperature, suggests that resources C substrate supply and water availability are more important than temperature in regulating interannual variations of soil C release in semiarid grassland ecosystems. The findings indicate that atmospheric N deposition may have the potential to mitigate soil C loss induced by increased precipitation, and highlight that long‐term and multi‐factor global change studies are critical for predicting the general patterns of terrestrial C cycling in response to global change in the future. Abstract : Increased precipitation and nitrogen addition interactively affected soil respiration. Response patterns of soil respiration to climate change varied with temporal scale. Carbon substrate supply controls the treatment‐induced changes on soil respiration.